Effects of salinity and external proline on seed germination and early growth of Cucumis sativus cv. super ps - FARIBA AMINI; MEHRY ASKARY; FAHIMEH MOHTASHAMI (Nusantara Bioscience, 2018)
Amini F, Askary M, Mohtashami F. 2018. Effects of salinity and external proline on seed germination and early growth of Cucumis sativus cv. super ps. Nusantara Bioscience 10: 215-220. Salinity is one of the important abiotic stresses that has an adverse effect on plant productions. High salt concentrations had negative effects on plant processes such as seed germination, seedling growth and turgescent, vegetative growth, flowering and fruiting stages. Proline as a compatible solution plays an important role in defense mechanisms of cellular stress. This study was done to evaluate effects of proline pretreatment (0 and 20 mM) in terms of salinity (0, 50, 100 and 150 mM) on cucumber cv. super ps. The obtained results proved that salinity treatments had significant effects on seed germination rate. On the contrary, application of proline had no significant effect on germination percentages of control and salt-stressed seeds. The root fresh weight and length of plant reduced with salinity increment while proline treatment had positive significant effects on the root dry as well as the fresh weight. Although, no significant variation was found in the root length and dry weight of cultivars treated with proline under salinity stresses. Meanwhile, the shoot length and dry weight of plants declined after salt-stressed treatments. While this condition increased the fresh weight of shoot. Proline treatments increased all of observed parameters but there were no significant variation found in the root length or dry weight of plants treated under saline stresses. The total soluble carbohydrate of plants had positive significant correlation with salt concentration, but the application of proline declined carbohydrate amounts in both salt-stressed and non-stressed plant. Salinity stress increased sodium, proline, protein contents and CAT enzyme, GPOX as well as MDA concentrations, while in the proline-treated plants salinity stresses had no significant effect on CAT, GPOX, MDA concentrations and internal proline amount.